ADVOCACY AND ENFORCEMENT OF CIVIL COURT DECISIONS - Ochilboev, Azizbek Bakhodirjon ugli (Educational Research in Universal Sciences, 2023)
This article examines the participation of the lawyer in the execution of the decisions of the Civil Court and also provides information about the powers of the lawyer, the deadlines for the submission of executive documents for execution, the actions to be taken by the lawyer in case the deadline for submitting the executive document for execution is missed.